2019
DOI: 10.1142/s0192415x19500885
|View full text |Cite
|
Sign up to set email alerts
|

How Ginsenosides Trigger Apoptosis in Human Lung Adenocarcinoma Cells

Abstract: Panax ginseng is a natural medicine that has been used globally for a long time. Moreover, several studies have reported the effective activity of ginseng in treating malignancies. Various agents containing ginseng were widely used as an antitumor treatment nowadays. Lung cancer is the most common fatal cancer in China, and lung adenocarcinoma is the most common histological type of non-small cell lung cancer (NSCLC). What’s worse, many patients may have a failed response to conventional therapy including chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…The WXF is a traditional Chinese medicine formula consisted of multiple components, which focuses on dispelling cold, supplementing yangqi, activating blood circulation and clearing blood stasis. It was observed that the active ingredients of the WXF components such as aconitine (Qi et al, 2018), ginsenoside Rh2 (Li et al, 2018;Li X. et al, 2020), Rg3 (Sun et al, 2017;Xiao et al, 2019), emodin (Zhang et al, 2019a) and Angelica polysaccharide (Zhang et al, 2019a) have anti-tumor activities. Previous studies have shown that WXF has specific anti-tumor properties (Zhang et al, 2019b), and that extracts of WXF retain these anti-tumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…The WXF is a traditional Chinese medicine formula consisted of multiple components, which focuses on dispelling cold, supplementing yangqi, activating blood circulation and clearing blood stasis. It was observed that the active ingredients of the WXF components such as aconitine (Qi et al, 2018), ginsenoside Rh2 (Li et al, 2018;Li X. et al, 2020), Rg3 (Sun et al, 2017;Xiao et al, 2019), emodin (Zhang et al, 2019a) and Angelica polysaccharide (Zhang et al, 2019a) have anti-tumor activities. Previous studies have shown that WXF has specific anti-tumor properties (Zhang et al, 2019b), and that extracts of WXF retain these anti-tumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…One chemical can trigger opposite effects according to different cell types and physiological status, which is considered as bidirectional regulation [ 141 ]. Many natural products share the bidirectional regulation effect, such as jaceosidin [ 142 ], curcumin [ 143 , 144 ], ginsenosides [ 145 , 146 ], and baicalin [ 147 , 148 ].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…In addition, ginseng and its active components are often used to enhance chemotherapy sensitivity and alleviate adverse symptoms [17,18]. Related mechanisms may be involved in triggering apoptosis in human lung adenocarcinoma cells, promoting macrophages' transformation from type M2 to type M1, and keeping balance between T1/ T2 T-helper cells [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%